Impact of organizational mission on innovation: Evidence from Guarantee Trust Bank, Nigeria - Iortimbir Aun, Isaac; Abdul, Falilat Ajoke; Mustapha, Yusuf Ismail; Oladipo, Ganiyu Taiwo (Faculty of Economics and Business, University of Muhammadiyah Malang, 2023)
The purpose of this study was to evaluate the effect of organizational mission as an element of organizational culture on the level of innovation in Nigerian banking. The questionnaire was designed using structured questions to gather data from employees at five Guarantee Trust bank branches in the metropolis of Ilorin, Kwara State, Nigeria. A total of 132 respondents participated in this study, and the OLS-based regression analysis revealed that the mission and the consistency of mission implementation have a significant effect on product and service innovation. Therefore, this study recommends that banks in Nigeria should give serious consideration to their vision and mission, and consistently implement the mission in all company operations.